2004
DOI: 10.1186/1742-4690-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Human T lymphotropic virus type-1 p30II alters cellular gene expression to selectively enhance signaling pathways that activate T lymphocytes

Abstract: We are the first to demonstrate that p30II, while repressing the expression of many genes, selectively activates key gene pathways involved in T-cell signaling/activation. Collectively, our data suggests that this complex retrovirus, associated with lymphoproliferative diseases, relies upon accessory gene products to modify cellular environment to promote clonal expansion of the virus genome and thus maintain proviral loads in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Future studies will further characterize p30 II -Myc/ TIP60 biochemical interactions and determine their roles in cell-cycle deregulation and transformation by HTLV-1. Collectively, these findings suggest that nucleolar p30 II functions as a post-transcriptional regulator of Tax/Rex mRNA (Nicot et al, 2004;Younis et al, 2004) and suggest that, through interactions with transcriptional cofactors such as p300/CBP and TIP60, p30 II may also influence RNA Pol II nucleoplasmic transcription complexes to modulate the expression of viral and cellular genes (Figure 3c) (Zhang et al, 2000Michael et al, 2004).…”
Section: Htlv-1 Orf I: P12 I a Modulator Of T-cell Immune Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will further characterize p30 II -Myc/ TIP60 biochemical interactions and determine their roles in cell-cycle deregulation and transformation by HTLV-1. Collectively, these findings suggest that nucleolar p30 II functions as a post-transcriptional regulator of Tax/Rex mRNA (Nicot et al, 2004;Younis et al, 2004) and suggest that, through interactions with transcriptional cofactors such as p300/CBP and TIP60, p30 II may also influence RNA Pol II nucleoplasmic transcription complexes to modulate the expression of viral and cellular genes (Figure 3c) (Zhang et al, 2000Michael et al, 2004).…”
Section: Htlv-1 Orf I: P12 I a Modulator Of T-cell Immune Functionsmentioning
confidence: 99%
“…The Gal4 (DBD)-p30 II fusion protein interacts with p300; likewise, HA-tagged p30 II was shown to coimmunoprecipitate with p300 and disrupt formation of Tax-p300-HTLV-1 21 bp repeat complexes in streptavidin-agarose pulldown experiments . Results of glutathione-S-transferase (GST) pull-down assays demonstrated that in vitro translated p30 II interacts with amino-acid residues 1-595 of GST-p300 and residues 451-682 of GST-CBP, which comprise the kinaseinducible exchange (KIX) domain of CBP that is known to bind to Tax (Kwok et al, 1996;Giebler et al, 1997;Harrod et al, 1998;Zhang et al, 2001;Michael et al, 2004) recently reported Affymetrix microarray gene expression analyses of Jurkat cells stably transduced with a lentiviral vector expressing p30 II . Their results indicate that p30 II represses many cellular genes, particularly adhesion molecules, such as integrins and cadherins, but increases the expression of certain target genes involved in T-cell activation and apoptosis (Michael et al, 2004).…”
Section: Htlv-1 Orf I: P12 I a Modulator Of T-cell Immune Functionsmentioning
confidence: 99%
“…Plasmids were transfected using SuperFect (Qiagen, Valencia, CA) according to the manufacturer's instructions. Transduction of 293T and Jurkat T cells with pWPT-IRES-GFP and pWPT-p30-HA-IRES-GFP was performed as described (20). For ectopic expression of p30, 293T cells were transfected with 10 g of pTriEx4-Neo (mock), pTriEx-Neo-S-GFP, or pTriEx4-Neo-S-p30-HA (Novagen, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…We reported that p30 differentially modulates the activity of HTLV-1 promoter-driven reporter genes (18) through its interaction with the transcriptional coactivator p300 (19). In Jurkat T cells, p30 alters the expression of a variety of cellular genes and also enhances signal pathways important for T cell growth and survival (20). Ectopically expressed p30 leads to the retention of tax/rex mRNA in the nucleus (15, 21).…”
mentioning
confidence: 99%
“…These proteins are important for in vivo viral infectivity, host cell activation, and regulation of gene transcription (Collins et al, 1998;Ciminale et al, 1999;Trovato et al, 1999;Albrecht et al, 2000Albrecht et al, , 2002Bartoe et al, 2000;D'Agostino et al, 2000;Zhang et al, 2000Zhang et al, , 2001Ding et al, 2002;Franchini et al, 2003;Kim et al, 2003;Michael et al, 2004;Nicot et al, 2004;Younis et al, 2004). The role of these accessory proteins in HTLV-1-mediated transformation has not been …”
Section: Htlv-1 Replication and Mechanisms Of Carcinogenesismentioning
confidence: 99%